Thieme Chemistry Journals Awardees – Where Are They Now?Rhodium-Catalyzed Synthesis of Unsymmetric Di(heteroaryl) Ethers Using Heteroaryl Exchange Reaction - Tanii, Saori; Arisawa, Mieko; Tougo, Takaya; Horiuchi, Kiyofumi; Yamaguchi, Masahiko (Synlett, 2017)
Unsymmetric di(heteroaryl) ethers were synthesized by the rhodium-catalyzed heteroaryl exchange reaction of heteroaryl aryl ethers and heteroaryl esters at equilibrium. Diverse unsymmetric di(heteroaryl) ethers containing five- and six-membered heteroarenes were obtained. Di(heteroaryl) ethers can be synthesized starting from diaryl ethers, because heteroaryl aryl ethers are obtained by the heteroaryl exchange reaction of diaryl ethers.
Keywords: unsymmetric di(heteroaryl) ethers; rhodium; heteroaryl exchange reaction; C–O bond cleavage; heteroaryl benzoates